2007
DOI: 10.1007/s10437-007-9016-7
|View full text |Cite
|
Sign up to set email alerts
|

Preserving Knowledge, not Objects: A Somali Perspective for Heritage Management and Archaeological Research

Abstract: This article argues that the Somali people have a distinctive view on heritage and a different approach to its preservation relevant to their society. It suggests that a locally appropriate theoretical framework for heritage management and archaeological research can only be achieved if this local approach is taken into consideration and integrated into archaeological and heritage methodologies. The lack of qualified Somalis and indigenous perspectives in the archaeological research and heritage management pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 11 publications
0
30
0
1
Order By: Relevance
“…In this displacement, people often have had to leave behind most of their material possessions. As most of the Somali have lived and/or still live a nomadic or seminomadic lifeway, they learn from a young age the significance of skills in making essential material culture (Mire 2007(Mire , 2011.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this displacement, people often have had to leave behind most of their material possessions. As most of the Somali have lived and/or still live a nomadic or seminomadic lifeway, they learn from a young age the significance of skills in making essential material culture (Mire 2007(Mire , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…These experiences, oral histories and memories are the heritage they carry wherever they go. I have called this the knowledge-centred approach to heritage (Mire 2007(Mire , 2011. It facilitates the transmission process of both tangible and intangible knowledge through time and space, and from generation to generation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…She found that it is knowledge about the historical objects which is the most important documentation to save, and not the object themselves. Mire conducted her survey on historical objects, by interviewing locals in Somalia and Somali refugees in Europe, and managed to obtain surprisingly many details about Somalian pre-historic objects (Mire 2007). Mire showed with this research that involving the 'locals' (where ever they are situated today) can contribute to archaeological research.…”
Section: The Invisiblementioning
confidence: 99%
“…Both sides include archaeologists, indigenous people, looters, collectors and the public, and both feel they are the rightful owners of illegally traded antiquities (Cameron 1997: 68), and that whatever they are doing to get hold of the antiquities is for the greater good -to save the antiquities. What is interesting is that they are always saving the antiquities from each other (see Elia 1997;Brodie et al 2001;Schuster 2005;Mire 2007). The local side wants to save the antiquities from their region or home country and want all or most objects situated abroad to be brought home.…”
Section: Local or Global History?mentioning
confidence: 99%